Optimal dietary concentration of chromium for alleviating the effect of heat stress on growth, carcass qualities, and some serum metabolites of broiler chickens - Şahin, Kazım; Şahin, Nurhan; Onderci, M; Gursu, F; Cikim, G (Springernature, 2002)
This study was conducted to determine the effects of chromium (chromium picolinate, CrPic) supplementation at various levels (0, 200, 400, 800, or 1200 p/kg of diet) on performance, carcass characteristics, and some serum metabolites of broiler chickens (Ross) reared under heat stress (32.8degreesC). One hundred fifty old male broilers were randomly assigned to 5 treatment groups, 3 replicates of 10 birds each. The birds were fed either a control diet or the control diet supplemented with either 200, 400, 800, or 1200 mug Cr/kg of diet. Increased supplemental chromium resulted in an increase in body weight (p = 0.01, linear), feed intake (p less than or equal to 0.05, linear), and carcass characteristics (p = 0.05, linear) and improved feed efficiency (p = 0.01, linear). Increased supplemental chromium decreased serum corticosterone concentration (p = 0.01, linear), whereas it increased serum insulin and T-3 and T-4 concentrations (p = 0.01). Serum glucose and cholesterol concentrations decreased (p = 0.01), whereas protein concentrations increased linearly (p = 0.001) with higher dietary chromium supplementation. Results of the present study conclude that a supplementation of diet with chromium at 1200 ppb can alleviate the detrimental effects of heat stress in broiler.
Keywords: chromium; heat stress; performance; thyroid; corticosterone; broilers